When China rules the world the end of the western world and the birth of a new global order - Jacques, Martin (New York Penguin Press, 2012)
Explains how China's ascendance as an economic superpower will alter the cultural, political, social, and ethnic balance of global power in the twenty-first century, unseating the West and in the process creating a whole new world.
Includes bibliographical references (p. 736-776) and index.
Keywords: Globalization -- Economic aspects -- China; China -- Economic conditions -- 2000-.; China -- Foreign relations -- 1976-.; China -- Foreign relations -- Western countries; China -- Politics and government -- 2002-.; Western countries -- Foreign relations -- China